2022
DOI: 10.3390/nu14020393
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Mediterranean Diet Adherence before and after Bariatric Surgery: A Narrative Review

Abstract: The population suffering from obesity is rapidly increasing all over the world. Bariatric surgery has shown to be the treatment of choice in patients with severe obesity. A Mediterranean diet has long been acknowledged to be one of the healthiest dietary patterns associated with a lower incidence of many chronic diseases. The aim of the present narrative review is to summarize the existing research on the clinical impact of a Mediterranean diet before and after bariatric surgery, focusing on its effects on wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Another limitation of our findings was that we did not include other individual-and neighborhood-level measures potentially related to weight loss after surgery, such as physical activity, eating behaviors, and access to parks and supermarkets [34,38], to understand whether individual-level self-reported indicators are the most important factors at the time of surgery that could determine %TWL. Self-reported physical activity [39] and adherence to a "Mediterranean-style diet" [40] are associated with more surgical weight loss and maintenance of that weight loss. In some studies, self-reported perceived neighborhood characteristics had a strong influence on energy-balance behaviors [28,41].…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of our findings was that we did not include other individual-and neighborhood-level measures potentially related to weight loss after surgery, such as physical activity, eating behaviors, and access to parks and supermarkets [34,38], to understand whether individual-level self-reported indicators are the most important factors at the time of surgery that could determine %TWL. Self-reported physical activity [39] and adherence to a "Mediterranean-style diet" [40] are associated with more surgical weight loss and maintenance of that weight loss. In some studies, self-reported perceived neighborhood characteristics had a strong influence on energy-balance behaviors [28,41].…”
Section: Discussionmentioning
confidence: 99%
“…However, research indicates that it may not be the most efficient method for rapid weight loss prior to BS [22]. By adopting a balanced, energy-controlled diet before the operation, similar to the Mediterranean diet, patients can improve their nutritional habits and enhance their nutritional status [23]. However, it may not be restrictive enough to help reduce body weight significantly and quickly before BS [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, diet is probably the most common approach in clinical practice and previous studies have already described the beneficial effect of a Mediterranean diet on weight loss before and after BS [20,21]. Some authors have reported that patients who show greater adherence to a diet before surgery are also those who lose more weight after surgery, for example, following a low-calorie diet (LCD) [22].…”
Section: Introductionmentioning
confidence: 99%